STRATEGIC FACTORS OF BANK SUSTAINABILITY: INSIGHTS FOR DEVELOPING COUNTRIES - Yanti, Mal Isnaini Sri Mey; Setyo, Riyanto; Indra, Siswanti; sugiyono (Bank Indonesia, 2025)
The banking sector is vital to sustainable development, yet integrating sustainability into banking strategies remains challenging, particularly in developing countries with limited resources. This study systematically reviews key strategic factors driving banking sustainability and the challenges and opportunities specific to emerging markets. The PRISMA protocol collected articles from Scopus and Web of Science (1990–2024), providing 98 content-analysis articles. The findings reveal an increasing focus on banking sustainability after adopting the UN Responsible Banking Principles in 2019. Content analysis identified six main strategic factors: organisational capital, bank specialisation capability, innovative technology capability, market capability, institutional capability, and ESG capability. These insights offer valuable guidance for bankers, policymakers, and researchers in shaping sustainable banking strategies. While limited to literature-based data, this study provides a foundation for future empirical research and context-specific applications.